THE CONSTRUCTION OF JAVANESE ISLAMIC ETHICS IN SERAT WEDHATAMA: KARL MANNHEIM'S SOCIOLOGY OF KNOWLEDGE APPROACH - Syihabuddin, Muhammad; Mustofa, M. Lutfi; Nurbaiti, Dwi; Wafi, Hasan Abdul (Al-Qalam, 2024)
As a ruler who contributed to the revival of Javanese culture, especially in literature, Mangkunegara IV is mentioned as a ruler and a poet. One of the largest and most famous of his many literary works is "Serat Wedhatama". "Serat Wedhatama" is a manifestation of Mangkunegara IV's concern and sensitivity to the situation of the people at that time who experienced a moral crisis due to the influx of foreign cultures, he wrote many teachings on virtuousness that were by the personality of the Javanese people. This study seeks to identify the concept of Javanese Islamic Ethics in "Serat Wedhatama" and its construction according to Karl Mannheim's sociological theory of knowledge. This research is a type of qualitative research by applying the literature study method. The results of this study indicate that the concepts carried out in the teachings of Javanese Islamic Ethics in "Serat Wedhatama" are in the form of life guidelines that are tailored to the personality of "Javanese" as well as containing teachings of Islamic values. The teachings of ethics in "Serat Wedhatama" contain the teachings of human ethics towards others and human ethics towards God. The construction of Islamic Ethical values in "Serat Wedhatama" when viewed with the sociological theory of knowledge of Karl Mannheim refers to the historical social background of Mangkunegara IV when compiling "Serat Wedhatama". From a historical point of view, a very influential factor is heredity. Mangkunegara IV had close kinship with the previous three rulers who were religious circles. Born from a religious family supporting Mangkunegara IV grew up with a religious spirit. Embedding of a religious soul since childhood influences the output of his thoughts. It is natural when Mangkunegara IV through "Serat Wedhatama" expects Javanese to behave according to their personality, as well as act according to the actions taught in Islam.